Analisis Kepuasan Nasabah yang dipengaruhi Nilai Pelanggan dan Kepercayaan Pelanggan serta Kualitas Pelayanan - Tatang Suhidayat; Azhar Affandi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2018)
Banking services are financial institutions as intermediation in financial services. It plays an essential role in enhancing the company's operational activities. People's credit bank, which is a financial service, contributes to the development of small and medium enterprises. Competition in financial services, especially people's credit banks, which is increasingly stringent requires increasing the quality of their services to increase their customer satisfaction. This study aims to determine the effect of service quality on customer value and trust as well as its implications on customer satisfaction analyzed by a survey approach to rural credit banks in the City/Regency of Bandung, West Bandung, and Cimahi. The samples are 384 customers with the Cluster Proportionate Stratified Random Sampling, which is processed by path analysis. The results indicate that there is a significant influence on the service quality to customer value and trust and its implications for customer satisfaction. The results of this study contribute to the development of a study in the marketing field, specifically customer satisfaction in the financial services sector as the people's credit bank.